Regarding Two Births of a Single Romance - Krikščiūnas, Povilas (Tautosakos darbai, 2019)
This publication deals with a popular Lithuanian romantic folksong Vien tik vosilkų žiedai (‘Only the Cornflower Blossoms’). The first part presents the author’s remarks on the history and spread of this song, while the second part comprises its nine variants. The Russian folklorists consider the song in question to be the folklorized version of a fragment from the poem by Aleksey Apuchtin “The Madman”. Peculiarities of such transformation are the subject of an article by the Russian anthropologist and folklore researcher Aleksandra Archipova, written in 2012 and discussing the Russian variants of this particular song. The Folklore Archives of the Institute of Lithuanian Literature and Folklore contain 41 variant of this song. Unfortunately, the Lithuanian folklore collectors have ignored the new kinds of folklore for a long time; therefore, such number of the variants more likely reflects these methodological principles of folklore collection rather than the real extent of the song’s popularity. However, such amount of the material, studied against the background of all the romantic folksongs recorded in Lithuania, allows for grasping the peculiarities of the folksong adaptation in the new cultural surroundings, which is the purpose of the present publication. Parallels between the Russian and Lithuanian song texts may be evident; however, a more detailed comparative research reveals certain newly acquired features of their content, poetics, and style. Since the article by Archipova dealing with the Russian variants is also published in this journal, the present comparison focuses mainly on the materials from other peoples collected from printed sources and the internet. The song fragments are inserted into the article as illustrations. The supplement in the end of the publication contains folksong texts along with their melodies, revealing a much greater musical variety in this song than used to be hitherto assumed.